Ceramic tile with super-thick-layer semi-transparent jade grease slurry coating luster
By adopting the tile preparation process of super-thick layer semi-permeable jade fat patina composed of jade fat dry grains, jade fat glaze slurry and jade fat particles, the problems of unstable quality and poor feel of the existing medium-thick glaze tile are solved, and the high-quality super-thick layer semi-permeable jade fat patina luster is achieved.
Patent Information
- Application Number
- CN202510367434.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-26
AI Technical Summary
In the prior art, it is difficult to prepare ceramic tiles with thick glaze, especially ceramic tiles with semi-transparent jade fat patellar luster, which have problems such as unstable product quality, poor hand feel, and excessively thick material layer with low light transmittance.
The super-thick layer of semi-transmissive jade-paste luster consisting of at least one of jade-fat dry grains, jade-fat glaze slurry and jade-fat particles is used to form a jade-fat effect layer with a thickness of 1.0 to 2.0 mm through specific application and firing processes. Combined with inkjet design and polishing process, the decorative effect and feel of the ceramic tiles are enhanced.
The production of super-thick layer of semi-transparent jade fat patina luster has been achieved, with the decorative effect of special jade textures. The jade fat patina is more natural, the surface texture is retained and polished to the entire surface, and the feel is moist and delicate.
Smart Images

Figure CN119874195A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ceramics, and in particular relates to a ceramic tile with an ultra-thick layer of semi-transparent jade slurry patina and gloss. Background Art
[0002] Currently, the general definitions of tile gloss in the architectural ceramics industry include bright, high-gloss, soft, and waxy lusters. Tiles with a jade-like patina are rare. Compared to traditional tiles, tiles with a jade-like patina have a soft, translucent sheen and a rich, aged jade-like texture, making them more popular with consumers. Achieving this jade-like patina requires a thick, fine glaze layer that must be free of bubbles and cracks. This thick glaze layer places higher demands on tile production. Generally, excessive glaze application can lead to uneven shrinkage during drying and firing, causing cracks or even flaking in the glaze surface. Alternatively, poor gas evacuation during firing can result in bubbles or pinholes on the surface, compromising both aesthetics and strength. A higher glaze application places greater stress on the green body, making it more susceptible to breakage and causing deformation of the tile during firing, impacting shape and dimensional accuracy.
[0003] The Chinese invention patent with publication number CN108129028A discloses a lustrous and thick-glazed ceramic product and its manufacturing process. The lustrous and thick-glazed ceramic product comprises a white porcelain body and a lustrous and thick glaze disposed outside the white porcelain body, wherein the thickness of the lustrous and thick glaze is 3 to 6 times that of the white porcelain body. The lustrous and thick-glazed ceramic product provided by the invention is obtained by selecting raw materials for the white porcelain body and the lustrous and thick glaze. The prepared lustrous and thick-glazed ceramic product has a thick and lustrous glaze surface, and the surface is bluish-green or bluish-white. When irradiated with strong light, the cotton-like texture in the glaze layer can be easily reflected through the white porcelain body. The product can be used as an art ornament, tea set or daily-use porcelain, and will form natural cracks after high-temperature use.
[0004] Chinese invention patent publication number CN111960862A discloses a multi-layer composite thick-glazed white porcelain and its production process. The multi-layer composite thick-glazed white porcelain utilizes a three-layer structure consisting of a base glaze layer, a connecting glaze layer, and a top glaze layer to increase the thickness of the white porcelain glaze surface. The connecting glaze layer has a melting temperature between the base and top glaze layers, tightly connecting the base and top glaze layers during firing without cracking the top glaze layer. The result is a thick-glazed white porcelain with a rich, lustrous color, a milky white pearly luster, and a smooth touch.
[0005] Existing technologies have difficulty producing ceramic tiles with thick glaze layers. In particular, producing ceramic tiles with a thick, semi-transparent, jade-like glaze patina often results in issues such as inconsistent product quality, a less than delicate feel, or excessively thick layers of material resulting in low light transmittance, or a gloss that is too bright or too matte. Optimizing existing technologies is necessary to produce ceramic tiles with an ultra-thick, semi-transparent, jade-like glaze patina. Summary of the Invention
[0006] The object of the present invention is to overcome at least one shortcoming of the prior art and to provide a ceramic tile with an ultra-thick layer of semi-transparent jade grease patina and gloss.
[0007] The technical solution adopted by the present invention is: A ceramic tile with an ultra-thick, semi-transparent jade glaze patina and luster, comprising a body and a jade-fat effect layer, wherein the jade-fat effect layer is formed from at least one of jade-fat dry particles, jade-fat glaze slurry, and jade-fat particles. A method for preparing the ceramic tile comprises the following steps: Applying glaze on the surface of the body in sequence, applying a jade-fat effect layer to a specified thickness on the entire surface or partially according to the design, drying and firing, wherein the jade-fat effect layer is composed of at least one of jade-fat dry particles and jade-fat glaze slurry, and when the jade-fat dry particles are applied for the first time, the wetting agent, the thickening agent and the jade-fat effect layer components are mixed in a mixing ratio of 5-10% by mass of the wetting agent, 2-3% by mass of the thickening agent and the remainder of the jade-fat effect layer components; or The powder particles are evenly distributed in a compacting machine, and the jade fat particles are spread on the entire surface or part of the surface to a desired thickness. According to the design, the flat surface or mold blank is pressed, and at least one of the jade fat dry particles and the jade fat glaze slurry is superimposed or not superimposed, and then dried and fired. in: The raw materials of the jade fat dry particles are composed by weight: 15-33 parts of potassium feldspar, 18-31 parts of sodium feldspar, 10-20 parts of quartz, 5-9 parts of zinc oxide, 4-15 parts of aluminum oxide, 3-7 parts of potassium carbonate, 5-11 parts of calcite, 6-13 parts of dolomite, 12-20 parts of barium carbonate, and 1-4 parts of strontium carbonate; The mass composition of the solid raw materials of the jade glaze slurry is as follows: 15-38 parts of potassium feldspar, 12-22 parts of sodium feldspar, 11-20 parts of quartz, 18-30 parts of nepheline, 9-15 parts of burnt clay, 3-8 parts of aluminum oxide, 13-21 parts of calcite, 6-19 parts of dolomite, 0-1 part of fluorite, 3-8 parts of wollastonite, 7-18 parts of barium carbonate, 0-2 parts of zirconium oxide, 1-4 parts of zinc oxide, and 3-10 parts of strontium carbonate; The raw materials of the jade fat particles are composed by weight: 18 to 27 parts of potassium feldspar, 10 to 23 parts of sodium feldspar, 2 to 11 parts of quartz, 20 to 33 parts of nepheline, 6 to 12 parts of kaolin, 3 to 8 parts of aluminum oxide, 11 to 26 parts of calcite, 12 to 23 parts of dolomite, 3 to 8 parts of wollastonite, 6 to 15 parts of barium carbonate, 4 to 11 parts of zinc oxide, and 3 to 10 parts of strontium carbonate.
[0008] In some examples, the chemical mass composition of the jade dry particles is: SiO2: 20-43%, Al2O3: 7-20%, K2O: 1-13%, Na2O: 1-11%, CaO: 8-30%, MgO: 2-10%, ZnO: 4-10%, BaO: 5-17%, SrO: 1-3%.
[0009] In some examples, the chemical mass composition of the solid components of the jade glaze slurry is: SiO2: 22~50%, Al2O3: 5~14%, K2O: 3~11%, Na2O: 3~13%, CaO: 8~17%, MgO: 7~13%, ZnO: 3~12%, BaO: 2~10%, SrO: 1~3%, ZrO: 0~1%.
[0010] In some instances, the chemical mass composition of the jade fat particles is: SiO2: 16-37%, Al2O3: 5-26%, K2O: 3-16%, Na2O: 4-18%, CaO: 6-18%, MgO: 3-15%, ZnO: 3-12%, BaO: 1-9%, SrO: 1-3%.
[0011] In some examples, the preparation method of the jade fat dry particles includes: weighing the jade fat dry particle raw materials according to a ratio, pouring them into a frit furnace, firing at 1420-1600° C. for 1-5 hours, and crushing and screening to obtain the jade fat dry particles.
[0012] In some examples, the preparation method of the jade glaze slurry includes: weighing the jade glaze slurry raw materials according to a ratio, pouring them into a ball mill, adding appropriate amounts of additives and water, ball milling and sieving to obtain the jade glaze slurry.
[0013] In some examples, the preparation method of the jade fat particles includes: weighing the jade fat particle raw materials according to the ratio, crushing and mixing, adding appropriate amounts of additives and water, granulating, drying, and screening to obtain the jade fat particles.
[0014] In some examples, the average particle size of the jade dry particles is 45 to 250 μm.
[0015] In some examples, the specific gravity of the jade glaze slurry is 1.28-1.65, and the viscosity at 25° C. is 39.43-67.02 cP.
[0016] In some examples, the average particle size of the jade fat particles is 105 to 330 μm.
[0017] In some examples, an inkjet printing layer and / or a protective glaze layer is further provided between the top glaze and the jade effect layer.
[0018] In some examples, 1-5% of corundum slurry is added to the final application of the jade effect layer to increase the glaze surface temperature and enhance the glaze surface wear resistance.
[0019] In some examples, the sintering temperature is 1130-1210°C.
[0020] In some examples, the sintering time is 30 to 70 minutes.
[0021] In some examples, the wetting agent is selected from wetting agent No. DSR1138 produced by Guangdong Daoshi Ceramic Materials Co., Ltd.
[0022] In some examples, the thickener is selected from thickener No. DS-9 produced by Guangdong Daoshi Ceramic Materials Co., Ltd.
[0023] In some examples, the thickness of the jade-fat effect layer is 1.0 to 2.0 mm.
[0024] In some examples, the fired tiles are polished using a fiber brush head, preferably a 60-mesh carbon fiber brush head.
[0025] The above features can be combined arbitrarily unless they conflict with each other.
[0026] The beneficial effects of the present invention are: The ceramic tiles with ultra-thick semi-transparent jade patina luster in some embodiments of the present invention have an ultra-thick (thickness of 1.0-2.0 mm) jade effect layer, which has a special jade-like texture after firing, providing a new decorative effect.
[0027] In some embodiments of the present invention, the ceramic tiles with an ultra-thick layer of semi-transparent jade patina luster are integrated with the inkjet design and the jade patina effect layer, making the jade patina effect of the ceramic tiles more natural.
[0028] In some embodiments of the present invention, the ceramic tiles with an ultra-thick layer of semi-transparent jade patina have a glossy jade effect layer with a natural texture on the surface after firing. The texture is retained through a brush-polishing process while the entire surface of the ceramic tile including the gaps is polished, giving it a smooth and lustrous feel. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a photograph of the tile sample of Example 1.
[0030] Figure 2 This is a photograph of the tile sample of Example 2.
[0031] Figure 3 This is a photograph of the tile sample of Example 3.
[0032] Figure 4 This is a photograph of the tile sample of Example 4.
[0033] Figure 5 This is a photograph of the tile sample of Example 5.
[0034] Figure 6 This is a photograph of the tile sample of Example 6.
[0035] Figure 7 This is a photograph of the tile sample of Comparative Example 1.
[0036] Figure 8 This is a photograph of the tile sample of Comparative Example 2.
[0037] Figure 9 This is a photograph of the tile sample of Comparative Example 3.
[0038] Figure 10 This is a photograph of the tile sample of Comparative Example 4.
[0039] Figure 11 This is a photograph of the tile sample of Comparative Example 5.
[0040] Figure 12 This is a photograph of the tile sample of Comparative Example 6.
[0041] Figure 13 This is a photograph of the tile sample of Comparative Example 7.
[0042] Figure 14 This is a photograph of the tile sample of Comparative Example 8. DETAILED DESCRIPTION
[0043] A ceramic tile with an ultra-thick, semi-transparent jade glaze patina and luster, comprising a body and a jade-fat effect layer, wherein the jade-fat effect layer is formed from at least one of jade-fat dry particles, jade-fat glaze slurry, and jade-fat particles. A method for preparing the ceramic tile comprises the following steps: Applying glaze on the surface of the body in sequence, applying a jade-fat effect layer to a specified thickness on the entire surface or partially according to the design, drying and firing, wherein the jade-fat effect layer is composed of at least one of jade-fat dry particles and jade-fat glaze slurry, and when the jade-fat dry particles are applied for the first time, the wetting agent, the thickening agent and the jade-fat effect layer components are mixed in a mixing ratio of 5-10% by mass of the wetting agent, 2-3% by mass of the thickening agent and the remainder of the jade-fat effect layer components; or The powder particles are evenly distributed in a compacting machine, and the jade fat particles are spread on the entire surface or part of the surface to a desired thickness. According to the design, the flat surface or mold blank is pressed, and at least one of the jade fat dry particles and the jade fat glaze slurry is superimposed or not superimposed, and then dried and fired. in: The raw materials of the jade fat dry particles are composed by weight: 15-33 parts of potassium feldspar, 18-31 parts of sodium feldspar, 10-20 parts of quartz, 5-9 parts of zinc oxide, 4-15 parts of aluminum oxide, 3-7 parts of potassium carbonate, 5-11 parts of calcite, 6-13 parts of dolomite, 12-20 parts of barium carbonate, and 1-4 parts of strontium carbonate; The mass composition of the solid raw materials of the jade glaze slurry is as follows: 15-38 parts of potassium feldspar, 12-22 parts of sodium feldspar, 11-20 parts of quartz, 18-30 parts of nepheline, 9-15 parts of burnt clay, 3-8 parts of aluminum oxide, 13-21 parts of calcite, 6-19 parts of dolomite, 0-1 part of fluorite, 3-8 parts of wollastonite, 7-18 parts of barium carbonate, 0-2 parts of zirconium oxide, 1-4 parts of zinc oxide, and 3-10 parts of strontium carbonate; The raw materials of the jade fat particles are composed by weight: 18 to 27 parts of potassium feldspar, 10 to 23 parts of sodium feldspar, 2 to 11 parts of quartz, 20 to 33 parts of nepheline, 6 to 12 parts of kaolin, 3 to 8 parts of aluminum oxide, 11 to 26 parts of calcite, 12 to 23 parts of dolomite, 3 to 8 parts of wollastonite, 6 to 15 parts of barium carbonate, 4 to 11 parts of zinc oxide, and 3 to 10 parts of strontium carbonate.
[0044] In order to obtain better decorative effects or different decorative effects, a surface glaze layer, a ceramic ink printing layer, a protective glaze layer, etc. can also be provided as needed.
[0045] The dried granules of jade are in granular form. In order to apply them better, they can be applied in multiple passes. Preferably, the thickness of each application is the same.
[0046] In the present invention, barium carbonate is introduced as the primary source of barium oxide in the composition. Barium oxide has the strongest fluxing effect among alkaline earth metal oxides, which can reduce the firing temperature of the product, aligning the glaze and body temperatures, and preventing the glaze from fully maturing and losing its gloss due to temperature mismatch. Adding barium carbonate to ceramics can reduce the formation of pores and bubbles, thereby improving the appearance quality and intrinsic performance of the ceramics. Furthermore, the addition of barium carbonate can improve the translucency of the ceramics, making the ceramic products appear more transparent.
[0047] Introducing strontium carbonate to provide strontium oxide helps reduce the material's viscosity, widen the melting and sintering range, extend the material's properties, and improve the material's compressive strength in the glass phase. Furthermore, strontium oxide, as a heavier element, can increase the material's refractive index.
[0048] Calcite and dolomite provide the divalent network oxides calcium oxide and magnesium oxide. At high temperatures, they release free oxygen, disrupting the network structure and reducing the viscosity of the material in the melt, facilitating its melting. The presence of a high calcium oxide content in the material improves its refractoriness and causes the jade-like effect layer to lose transparency after firing, giving it the texture of aged jade.
[0049] Nepheline, also known as nepheline syenite, is a rare potassium- and sodium-rich aluminosilicate mineral. Compared to albite and potassium feldspar, nepheline has higher contents of potassium oxide, sodium oxide, and aluminum oxide, giving it unique physical and chemical properties. Using a high concentration of nepheline in jade glaze and jade granules can relatively lower the material's melting temperature, resulting in a delicate and soft jade effect layer.
[0050] In some examples, the chemical mass composition of the jade dry particles is: SiO2: 20-43%, Al2O3: 7-20%, K2O: 1-13%, Na2O: 1-11%, CaO: 8-30%, MgO: 2-10%, ZnO: 4-10%, BaO: 5-17%, SrO: 1-3%.
[0051] In some examples, the chemical mass composition of the solid components of the jade glaze slurry is: SiO2: 22~50%, Al2O3: 5~14%, K2O: 3~11%, Na2O: 3~13%, CaO: 8~17%, MgO: 7~13%, ZnO: 3~12%, BaO: 2~10%, SrO: 1~3%, ZrO: 0~1%.
[0052] In some instances, the chemical mass composition of the jade fat particles is: SiO2: 16-37%, Al2O3: 5-26%, K2O: 3-16%, Na2O: 4-18%, CaO: 6-18%, MgO: 3-15%, ZnO: 3-12%, BaO: 1-9%, SrO: 1-3%.
[0053] In some examples, the preparation method of the jade fat dry granules includes: weighing the jade fat dry granules according to a ratio, pouring them into a frit furnace, calcining them at 1420-1600°C for 1-5 hours, and then crushing and screening them to obtain the jade fat dry granules. The melted jade fat dry granules have stable properties and are conducive to obtaining a high-quality jade fat effect layer.
[0054] In some examples, the preparation method of the jade glaze slurry includes: weighing the jade glaze slurry raw materials according to a ratio, pouring them into a ball mill, adding appropriate amounts of additives and water, ball milling and sieving to obtain the jade glaze slurry.
[0055] In some examples, the preparation method of the jade fat granules includes: weighing jade fat granule raw materials according to a ratio, crushing and mixing, adding an appropriate amount of additives and water, granulating, drying, and screening to obtain the jade fat granules. The jade fat granules can better control the thickness of the jade fat effect layer.
[0056] In some examples, the preparation process of ceramic tiles includes: pouring or spraying glaze on the body and then inkjet printing, applying protective glaze, applying glue and jade fat dry particles on the entire surface or partially according to the design, repeatedly applying the glue to the required thickness, spraying glue to fix it, drying, and firing.
[0057] In some examples, the preparation process of ceramic tiles includes: pouring or spraying glaze on the body and then inkjet printing, applying protective glaze, printing sunken ink according to the design, and then applying jade fat dry particles on the entire surface or partially to the required thickness, spraying glue to fix it, and drying and firing.
[0058] In some examples, the preparation process of the ceramic tile includes: pouring or spraying glaze on the body and then inkjet printing, applying jade glaze slurry, applying jade glaze slurry of required thickness on the entire surface or part of the body, drying, and firing.
[0059] In some instances, the ceramic tile preparation process includes: evenly distributing the powder particles in a pressing machine, spreading the jade particles of the desired thickness on the entire surface or part of the surface, pressing into a flat surface or mold blank according to the design, inkjet printing according to the design, applying a protective glaze, superimposing or not superimposing the jade dry particles and jade glaze, drying, and firing.
[0060] Jade fat dry particles, jade fat glaze slurry and jade fat particles can be mixed and used. For example, jade fat particles can be laid on the bottom layer first, and then jade fat glaze slurry can be applied, followed by jade fat dry particles.
[0061] In some examples, the preparation process of the ceramic tile includes: applying jade glaze after pouring or spraying glaze on the body, inkjet printing, applying jade glaze of desired thickness on the entire surface or part of the body, and drying and firing.
[0062] In some examples, the average particle size of the dried jade fat particles is 45 to 250 μm, which is convenient for spreading.
[0063] In some examples, the specific gravity of the jade glaze slurry is 1.28-1.65, and the viscosity at 25° C. is 39.43-67.02 cP, which is conducive to glazing.
[0064] In some examples, the average particle size of the jade fat particles is 105 to 330 μm.
[0065] In some examples, an inkjet printing layer and / or a protective glaze layer is further provided between the top glaze and the jade effect layer.
[0066] In some examples, 1-5% of corundum slurry is added to the final application of the jade effect layer to increase the glaze surface temperature and enhance the glaze surface wear resistance.
[0067] In some examples, the sintering temperature is 1130-1210°C.
[0068] In some examples, the sintering time is 30 to 70 minutes.
[0069] The type of wetting agent is not particularly limited. In some embodiments, the wetting agent is selected from wetting agent No. DSR1138 produced by Guangdong Daoshi Ceramic Materials Co., Ltd. This wetting agent has a good wetting effect and is a better choice.
[0070] The function of the thickener is to adjust the fluidity of the dry granular glaze, and the amount of the thickener used can be adjusted accordingly according to the viscosity of the glaze. In some examples, the thickener is selected from the thickener No. DS-9 of Guangdong Daoshi Ceramic Materials Co., Ltd.
[0071] In some examples, the thickness of the jade-fat effect layer is 1.0 to 2.0 mm, which can achieve a better jade-fat effect.
[0072] In some examples, the fired tiles are polished using a fiber brush head, preferably a 60-mesh carbon fiber brush head.
[0073] The above features can be combined arbitrarily unless they conflict with each other.
[0074] The following disclosure provides various embodiments or examples to implement different aspects of the present invention.
[0075] In the following examples, unless otherwise specified, the parts stated are parts by mass and the percentages are all percentages by mass; 7% wetting agent DSR1138 and 2% thickener DS-9 were added to the first jade-fat effect layer, and 4% corundum slurry was added to the last jade-fat effect layer; the specific gravity of the jade-fat glaze slurry was 1.28-1.65, and the viscosity at 25°C was 39.43-67.02 cP.
[0076] The jade fat materials of the jade fat effect layer in different examples are as follows: The jade fat material used in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 is in the form of jade fat dry particles, and the raw material mass fractions of the jade fat dry particles used are as follows: 19 parts of potassium feldspar, 3 parts of potassium carbonate, 24 parts of sodium feldspar, 17 parts of quartz, 7 parts of aluminum oxide, 8 parts of zinc oxide, 10 parts of calcite, 7 parts of dolomite, 15 parts of barium carbonate, and 2 parts of strontium carbonate.
[0077] The jade fat material used in Example 3, Example 4, Comparative Example 3 and Comparative Example 4 is in the form of jade fat glaze slurry, which is uniformly obtained by ball milling 100 parts of solid raw materials, 40 parts of water, 0.15 parts of sodium carboxymethyl cellulose, and 0.35 parts of sodium tripolyphosphate. The mass fraction of the solid raw materials in the jade fat glaze slurry is as follows: 27 parts of potassium feldspar, 16 parts of sodium feldspar, 14 parts of quartz, 28 parts of nepheline, 10 parts of burnt clay, 3 parts of aluminum oxide, 2 parts of zinc oxide, 16 parts of calcite, 6 parts of dolomite, 1 part of fluorite, 3 parts of wollastonite, 9 parts of barium carbonate, 4 parts of strontium carbonate, and 1 part of zirconium oxide.
[0078] The jade fat material used in Example 5, Example 6 and Comparative Example 5 is in the form of jade fat particles, and the raw material mass fractions of the jade fat particles used are as follows: 22 parts of potassium feldspar, 13 parts of sodium feldspar, 5 parts of quartz, 25 parts of nepheline, 10 parts of kaolin, 4 parts of aluminum oxide, 6 parts of zinc oxide, 19 parts of calcite, 18 parts of dolomite, 5 parts of wollastonite, 10 parts of barium carbonate, and 4 parts of strontium carbonate.
[0079] The preparation methods of different examples are as follows. For the sake of comparison, the firing conditions of each example are unified as a conventional roller kiln surface temperature of 1165°C for 50 min. Example 1
[0080] Process flow: blank → glaze → inkjet design → spray protective glaze → apply jade fat dry particles (4 times) → spray glue to fix → drying → firing → carbon fiber brush polishing.
[0081] The step of applying the jade fat dry granules was repeated 4 times, making the overall thickness of the jade fat dry granules to be 1.5 mm. Figure 1 It can be seen that the jade fat effect is delicate and soft. Example 2
[0082] Process flow: blank → top glaze → inkjet design → spray protective glaze → print sinking ink → apply jade fat dry particles (4 times) → spray glue to fix → drying → firing → carbon fiber brush polishing.
[0083] After printing the sunken ink, the step of applying the jade dry particles was repeated 4 times to make the overall thickness of the jade dry particles 1.5 mm. Figure 2 It can be seen that the jade fat effect is delicate and soft. Example 3
[0084] Process flow: blank → top glaze → application of jade glaze → inkjet design → spray protective glaze → application of jade glaze slurry (3 times) → firing → carbon fiber brush polishing.
[0085] The thickness of the first coat of jade glaze slurry is 0.5mm, the thickness of the second coat of jade glaze slurry is 1.0mm, and the thickness of the last coat of jade glaze slurry is 0.2mm, making the total thickness of the jade glaze slurry 1.7mm. Figure 3 It can be seen that the jade fat effect is delicate and soft. Example 4
[0086] Process flow: blank → top glaze → inkjet design → spray protective glaze → apply jade glaze slurry (4 times) → firing → carbon fiber brush polishing.
[0087] The jade fat glaze slurry step was repeated 4 times to make the overall thickness of the jade fat dry particles 1.5 mm. Figure 4 It can be seen that the jade fat effect is delicate and soft. Example 5
[0088] Process flow: green body particles → jade fat particles (1 time) → pressing and molding → inkjet printing → protective glaze → firing → carbon fiber brush polishing.
[0089] The overall thickness of the jade fat particles is 1.0 mm. Figure 5 It can be seen that the jade fat effect is delicate and soft. Example 6
[0090] Process flow: green body particles → jade fat particles (1 time) → pressing and molding → inkjet printing → protective glaze → applying jade fat dry particles / jade fat glaze slurry → firing → carbon fiber brush polishing.
[0091] The thickness of the jade particle cloth is 1.0mm. Figure 6 It can be seen that the jade fat effect is delicate and soft. Comparative Example 1
[0092] Process flow: blank → glaze → inkjet design → spray protective glaze → print sinking ink → apply jade fat dry particles (3 times) → spray glue to fix → drying → firing → carbon fiber brush polishing.
[0093] The step of applying the jade granules was repeated 3 times to make the overall thickness of the jade granules 0.8 mm. Figure 7 It can be seen that the glaze surface of the fired material is thin and the jade feel is weak. Comparative Example 2
[0094] Process flow: blank → glaze → inkjet design → spray protective glaze → print sinking ink → apply jade fat dry particles (8 times) → spray glue to fix → drying → firing → carbon fiber brush polishing.
[0095] The printing and sinking ink application jade dry granules step was repeated 8 times, so that the overall thickness of the jade dry granules was 2.3 mm. Figure 8 It can be seen that the concave and convex feeling created by the sunken ink after multiple inkjet printing and then covering is weakened, and the dry particle layer is too thick and has poor light transmittance, and cannot show the semi-transparency of the jade patina. Comparative Example 3
[0096] Process flow: blank → top glaze → apply jade glaze slurry (1 time) → inkjet design → spray protective glaze → apply jade glaze slurry (2 times) → firing → carbon fiber brush polishing.
[0097] The thickness of the first layer of jade glaze slurry is 0.3mm, and the thickness of the last layer of jade glaze slurry is 0.3mm, so that the overall thickness of the jade glaze slurry is 0.6mm. Figure 9 It can be seen that the inkjet design reduces the vertical blending space between the two layers of jade glaze, and the effect is relatively stiff. Comparative Example 4
[0098] Process flow: blank → top glaze → inkjet design → spray protective glaze → apply jade glaze slurry (8 times) → firing → carbon fiber brush polishing.
[0099] The step of applying jade fat dry particles was repeated 8 times to make the overall thickness of the jade fat dry particles 2.3 mm. Figure 10 It can be seen that the glaze layer accumulates and becomes more opaque, and the underglaze inkjet design is blocked by the overly thick glaze layer, affecting the effect. Comparative Example 5
[0100] Process flow: green body particles → jade fat particles (1 time) → pressing and molding → inkjet printing → protective glaze → applying jade fat dry particles / jade fat glaze slurry → firing.
[0101] The overall thickness of the jade fat particles is 1.0 mm. Figure 11 It can be seen that there are holes on the surface of the tiles. Comparative Example 6
[0102] Process flow: blank → glaze → inkjet design → spray protective glaze → apply jade fat dry particles (4 times) → spray glue to fix → drying → firing → carbon fiber brush polishing.
[0103] The thickness of the jade granules is 1.5 mm, and the formula is the same as that of Example 1. No wetting agent or thickener is added to the first coat of jade granules. When the cloth is applied, the contact surface is relatively dry, the water is absorbed quickly, and the glaze surface is uneven. Figure 12 It can be seen that cracks appeared locally on the bricks during drying, the jade effect layer curled up, and after firing, the glaze surface was uneven and there was glaze shrinkage. Comparative Example 7
[0104] Process flow: blank → glaze → inkjet design → spray protective glaze → apply jade fat dry particles (4 times) → spray glue to fix → drying → firing → carbon fiber brush polishing.
[0105] The thickness of the jade granules is 1.5 mm, and the formula is the same as that in Example 1. 20% wetting agent and 5% thickener are added to the first course of jade granules. Figure 13 It can be seen that the dry granular glaze is too thick, resulting in uneven distribution and the required drying time is prolonged, which is not conducive to production. Comparative Example 8
[0106] Process flow: blank → glaze → inkjet design → spray protective glaze → apply jade fat dry particles (4 times) → spray glue to fix → drying → firing → carbon fiber brush polishing.
[0107] The thickness of the jade dry granules was 1.5 mm, and the formula was the same as in Example 1, except that no corundum slurry was added to the final jade dry granules. Figure 14 It can be seen that the glaze hardness is relatively low and scratches are easy to appear.
[0108] The above is a further detailed description of the present invention and should not be considered as a limitation on the specific implementation of the present invention. For those skilled in the art, simple deductions or substitutions that do not depart from the concept of the present invention are within the scope of protection of the present invention.
Claims
1. A ceramic tile with an ultra-thick layer of semi-transparent jade patina luster, characterized in that: The ceramic tile comprises a body and a jade-fat effect layer, wherein the jade-fat effect layer is formed by at least one of jade-fat dry particles, jade-fat glaze slurry and jade-fat particles. The preparation method of the ceramic tile comprises the following steps: Apply glaze on the surface of the blank in sequence, apply a jade-fat effect layer to a specified thickness on the entire surface or partially according to the design, dry and sinter, the jade-fat effect layer is composed of at least one of jade-fat dry particles and jade-fat glaze slurry, and when the jade-fat dry particles are applied for the first time, the wetting agent, the thickener and the jade-fat effect layer components are mixed in a mixing ratio of 5-10% by mass of the wetting agent, 2-3% by mass of the thickener and the remainder of the jade-fat effect layer components; or The powder particles are evenly distributed in a press, and the jade fat particles of the required thickness are spread on the entire surface or part of the surface, and the surface is pressed into a plane or mold blank according to the design, and at least one of the jade fat dry particles and the jade fat glaze slurry is superimposed or not superimposed, and then dried and fired; in: The raw materials of the jade fat dry particles are composed by weight: 15 to 33 parts of potassium feldspar, 18 to 31 parts of sodium feldspar, 10 to 20 parts of quartz, 5 to 9 parts of zinc oxide, 4 to 15 parts of aluminum oxide, 3 to 7 parts of potassium carbonate, 5 to 11 parts of calcite, 6 to 13 parts of dolomite, 12 to 20 parts of barium carbonate, and 1 to 4 parts of strontium carbonate; The mass fraction of the solid raw materials of the jade glaze slurry is as follows: 15-38 parts of potassium feldspar, 12-22 parts of sodium feldspar, 11-20 parts of quartz, 18-30 parts of nepheline, 9-15 parts of burnt clay, 3-8 parts of aluminum oxide, 13-21 parts of calcite, 6-19 parts of dolomite, 0-1 part of fluorite, 3-8 parts of wollastonite, 7-18 parts of barium carbonate, 0-2 parts of zirconium oxide, 1-4 parts of zinc oxide, and 3-10 parts of strontium carbonate; The raw materials of the jade fat particles are composed in mass parts: 18 to 27 parts of potassium feldspar, 10 to 23 parts of sodium feldspar, 2 to 11 parts of quartz, 20 to 33 parts of nepheline, 6 to 12 parts of kaolin, 3 to 8 parts of aluminum oxide, 11 to 26 parts of calcite, 12 to 23 parts of dolomite, 3 to 8 parts of wollastonite, 6 to 15 parts of barium carbonate, 4 to 11 parts of zinc oxide, and 3 to 10 parts of strontium carbonate.
2. The ceramic tile according to claim 1, characterized in that: The chemical mass composition of the jade fat dry particles is: SiO2: 20-43%, Al2O3: 7-20%, K2O: 1-13%, Na2O: 1-11%, CaO: 8-30%, MgO: 2-10%, ZnO: 4-10%, BaO: 5-17%, SrO: 1-3%; The chemical mass composition of the solid components of the jade glaze slurry is: SiO2: 22-50%, Al2O3: 5-14%, K2O: 3-11%, Na2O: 3-13%, CaO: 8-17%, MgO: 7-13%, ZnO: 3-12%, BaO: 2-10%, SrO: 1-3%, ZrO: 0-1%; The chemical mass composition of the jade fat particles is: SiO2: 16-37%, Al2O3: 5-26%, K2O: 3-16%, Na2O: 4-18%, CaO: 6-18%, MgO: 3-15%, ZnO: 3-12%, BaO: 1-9%, SrO: 1-3%.
3. The ceramic tile according to claim 1 or 2, characterized in that: The preparation method of the jade dry granules comprises: weighing the jade dry granule raw materials according to the proportion, pouring them into a frit furnace, calcining at 1420-1600°C for 1-5 hours, crushing and screening to obtain the jade dry granules; The preparation method of the jade glaze slurry comprises: weighing the raw materials of the jade glaze slurry according to the proportion, pouring the raw materials into a ball mill, adding an appropriate amount of additives and water, ball milling and sieving to obtain the jade glaze slurry; The preparation method of the jade fat particles comprises: weighing the jade fat particle raw materials according to the proportion, crushing and mixing, adding a proper amount of additives and water, granulating, drying and screening to obtain the jade fat particles.
4. The ceramic tile according to claim 1 or 2, characterized in that: The average particle size of the jade fat dry particles is 45 to 250 μm; The specific gravity of the jade glaze slurry is 1.28-1.65, and the viscosity at 25°C is 39.43-67.02 cP; The average particle size of the jade fat particles is 105-330 μm.
5. The ceramic tile according to claim 1, characterized in that: An inkjet printing layer and / or a protective glaze layer is also provided between the surface glaze and the jade-fat effect layer.
6. The ceramic tile according to claim 1, 2 or 5, characterized in that: 1-5% of corundum slurry is added to the final application of the jade effect layer to increase the glaze surface temperature and enhance the glaze surface wear resistance.
7. The ceramic tile according to claim 1, 2 or 5, characterized in that: The sintering temperature is 1130-1210°C.
8. The ceramic tile according to claim 1, 2 or 5, characterized in that: The sintering time is 30 to 70 minutes.
9. The ceramic tile according to claim 1, 2 or 5, characterized in that: The thickness of the jade-fat effect layer is 1.0 to 2.0 mm.
10. The ceramic tile according to claim 1, 2 or 5, characterized in that: The wetting agent is selected from the wetting agent No. DSR1138 of Guangdong Dow Ceramic Materials Co., Ltd., and / or the thickener is selected from the thickener No. DS-9 of Guangdong Dow Ceramic Materials Co., Ltd.
Citation Information
Patent Citations
Bright and smooth thick glaze ceramic product and manufacturing process thereof
CN108129028A
Multi-layer composite thick-glaze white porcelain and manufacturing process thereof
CN111960862A
Jade texture semi-transparent ceramic material and production method thereof and application
CN101671161A
Semi-transparent silk-screen printed and brushed grease glossy ceramic tile and preparation method thereof
CN117164384A
Pure flat wear-resistant jade ceramic tile and preparation method thereof
CN119661254A
Cited By
Jade ceramic tile with soft fat effect and preparation method of jade ceramic tile
CN120607414A
Ceramic tile with a wax effect and method for its production
CN120607414B